Low Temperature Influence on Long Channel STI Last Process Relaxed and Strained Ge pFinFETs - Oliveira, A. V.; Agopian, P. G. D. [UNESP]; Martino, J. A.; Simoen, E.; Mitard, J.; Witters, L.; Collaert, N.; Claeys, C.; IEEE (Ieee, 2017)
The operation of germanium p-type channel FinFETs with two types of different channels, namely, relaxed and strained, is compared from room temperature down to 77 K. The most interesting finding is a higher I-ON over I-OFF ratio for the strained device, achieving around three orders of magnitude higher value than the relaxed channel at 77 K thanks to the strong hole mobility enhancement and thermal deactivation of the off-state current at low temperature.
Keywords: FinFET; germanium channel; low temperature; I-ON/I-OFF ratio; relaxed; strained